The relationship between macronutrient and micronutrient intake with anemia in the Puruk Cahu health center - Rino, Rino; Triawanti, Triawanti; Panghiyangani, Roselina; Noor, Meitria Syahadatina; Suhartono, Eko (Science Midwifery, 2024)
Adolescents constitute a vulnerable demographic group susceptible to iron deficiency owing to heightened nutritional demands during their growth phase. These requirements persist until the onset of puberty. The considerable prevalence of anemia among adolescents may persist into adulthood if not effectively managed. Within the working area of the Puruk Cahu Puskesmas, 20.68% of junior high school students are afflicted with anemia. This study aims to scrutinize the correlation between protein, iron, vitamin C, folic acid, and vitamin B12 levels and anemia among junior high school students in the aforementioned locale. Employing an analytical observational approach with a cross-sectional design, the study sampled 102 individuals through purposive sampling. Data collection utilized a questionnaire. Independent variables encompassed protein, iron, vitamin C, folic acid, and vitamin B12. Bivariate analysis was conducted utilizing the chi-square method, with multivariate analysis employing multiple logistic regression. Findings unveiled significant associations between protein (p=0.009), iron (p=0.008), and vitamin B12 (p=0.026) levels and anemia, whereas no such correlation was found with vitamin C (p=0.196) and folic acid. Iron emerged as the most influential factor contributing to anemia among junior high school students (Exp(B)=8.747). Consequently, this underscores the imperative of addressing iron deficiency within this demographic to alleviate anemia prevalence.